Preparation and Reaction of Fluorescently-Labeled Chitosan Nano Particles - Sun, Hong; Yun Liu, Xue; Zhu, Dechun; Gao, Daming; Ding, Ming (Asian Journal of Chemistry, 2013)
Chitosan nano particles were prepared firstly through the electrostatic interaction between chitosan polycation and sodium tripolyphosphate and then fluorescently-labeled chitosan nano particles was made by the reaction between the primary amino group (2-NH2) of chitosan and isothiocyanate root (N=C=S) of fluorescein isothiocyanate. Finally the effects of reaction time and chitosan concentration on the fluorescence labeling efficiency of chitosan were discussed. The results showed that various reaction times and chitosan concentrations had great effects on the structure and fluorescence labeling efficiency of chitosan nano particles.